Pengolahan Sampah Organik Menggunakan Maggot BSF sebagai Pakan Ikan Alternatif pada Desa Lesmana, Banyumas - Andrianto, Dimas; Yusriya, Rifqi; Daeli, Gavriel Allenfar; Prasetyo, Dwiandra Hadi; Firmansyah, Muhammad Ade; Nayanda, Najwa Putri; Qolbiyah, Syifa Ainul; Putri, Salsabila Yasmin Budi; Assa’addah, Habibah (Jurnal Pusat Inovasi Masyarakat, 2024)
Organic waste has become a significant problem in Lesmana Village, Ajibarang District, Banyumas Regency, West Java Province, Indonesia. The treatment of organic wastes needs to be done by various means, one of them using black soldier fly (Hermetia illucens) maggots. The training in maggot farming aimed to explore maggot potency as a decomposing agent in organic waste treatment, and analyzed the factors affecting the process, including environment, type of waste, and operational scale. The establishment of maggot farming has the potencial to be developed as an alternative fish pellet with high protein content. The community service methods involved eight persons from a community self-help group (Kelompok Swadaya Masyarakat), namely Berkah Runtah in Lesmana Village, who participated in the education seminar on 2nd July and continuous maggot farm training in July 2024. Besides the training, a seminar about using maggot as fish pellets was also held on 15th July to increase community knowledge about maggot use as a fish pellet. The farming cage size was 1.5 m x 1 m x 0.5 m, which was also an output of this activity. In conclusion, education and implementation of organic waste treatment using maggots in Lesmana Village showed great potency in establishing sustainable organic waste treatment as well as empowerment of society.